In-Lane Localization and Ego-Lane Identification Method Based on Highway Lane Endpoints - Kyoungtaek Choi; Jae Kyu Suhr; Ho Gi Jung (Journal of Advanced Transportation)
The low-cost global navigation satellite systems combined with an inertial navigation system (GNSS/INS) used most frequently for vehicle localization show errors up to 10 m, approximately, even in open-sky environments such as highways. To reduce this error on highways, this paper proposes a localization method based on lane endpoints. Since a lane endpoint frequently appears on a road and can be detected in close proximity even by a low-cost monocular camera, it is a very useful landmark for precise localization. However, the lane width is generally less than 3.5 m, and the localization error from the GNSS is about 10 m. Therefore, if an ego-lane is not identified, the lane endpoints detected in an ego-lane can be falsely corresponded to the lane endpoints in the other lane of a map. This paper proposes an in-lane localization method that uses lane endpoints, the relation between a camera and a road, and the estimated vehicle’s orientation from a map. In addition, this paper proposes an ego-lane identification method that generates a hypothesis about an ego vehicle position per lane by using the proposed in-lane localization method and verifies each hypothesis by the projection of lane endpoints and an additional landmark such as a road sign. The average error of the proposed in-lane localization method is 0.248 m on highways. The success rate of the proposed ego-lane identification method is 99.28% by one trial and reaches 100% by fusing the results.